Towards 5G: A Photonic Based Millimeter Wave Signal Generation for Applying in 5G Access Fronthaul - Alavi, S.E.; Soltanian, M.R.K.; Amiri, I.S.; Khalily, M.; Supa'at, A.S.M.; Ahmad, Harith (Nature Publishing Group, 2016)
5G communications require a multi Gb/s data transmission in its small cells. For this purpose millimeter wave (mm-wave) RF signals are the best solutions to be utilized for high speed data transmission. Generation of these high frequency RF signals is challenging in electrical domain therefore photonic generation of these signals is more studied. In this work, a photonic based simple and robust method for generating millimeter waves applicable in 5G access fronthaul is presented. Besides generating of the mm-wave signal in the 60 GHz frequency band the radio over fiber (RoF) system for transmission of orthogonal frequency division multiplexing (OFDM) with 5 GHz bandwidth is presented. For the purpose of wireless transmission for 5G application the required antenna is designed and developed. The total system performance in one small cell was studied and the error vector magnitude (EVM) of the system was evaluated.